Formulation of Chewable Tablets Containing Carbamazepine-β-cyclodextrin Inclusion Complex and F-Melt Disintegration Excipient. The Mathematical Modeling of the Release Kinetics of Carbamazepine - Adina Magdalena Musuc; Valentina Anuta; Irina Atkinson; Iulian Sarbu; Vlad Tudor Popa; Cornel Munteanu; Constantin Mircioiu; Emma Adriana Ozon; George Mihai Nitulescu; Mirela Adriana Mitu (MDPI AG, 2021)
Due to its low solubility, carbamazepine (CBZ) exhibits slow and incomplete release in the gastrointestinal tract and, hence, variable pharmacokinetics and pharmacodynamic effect. Lots of methods have been devised to improve its solubility, the large number of proposed solutions being a sign that the problem is not yet satisfactorily solved. The persistent problem is that predictable release kinetics, an increased rate but within defined limits, are required to avoid high absorption variability. This paper presents a synthesis of a carbamazepine-β-cyclodextrin inclusion complex (CBZ-β-CD), the characterization of the physical mixture, CBZ, β-CD and the CBZ-β-CD inclusion complex using Fourier transform infrared spectroscopy, scanning electron microscopy, simultaneous thermal analysis and X-ray diffraction, formulation of chewable tablets, determination of the dissolution of carbamazepine in medium containing 1% sodium lauryl sulfate (LSS), and in simulated saliva (SS), mathematical modeling of release kinetics. The kinetics of total CBZ release from tablets containing CBZ-β-CD and super-disintegrant F-Melt in both SS and LSS followed two steps: a burst release in the first minutes and a slower release in intervals up to 60 min. The release in the second phase has been well described by the Higuchi and Peppas models, which advocate a controlled release by combined diffusion and with some phenomena of swelling and relaxation of the matrix generated by the crospovidone component of the F-Melt excipient.